Ceramics in America 2014 - Hunter, Robert
Now in its fifteenth year of publication, Ceramics in America is considered the journal of record for historical ceramics scholarship in the American context and is intended for collectors, historical archaeologists, curators, decorative arts students, social historians, and contemporary potters. The 2014 volume of Ceramics in America will feature a series of 10 essays by ceramic specialists who are widely recognized in their respective fields of expertise. Each essay will examine 10 objects that are of particular significance to the author. In addition, other experts have been asked to contribute annotated bibliographies of their most significant reference works.